ORGANIZATION OF CREDIT OBLIGATIONS AND MONITORING OF COMMERCIAL BANKS - Baxriddin Jurayevich, Mahmudov; Mukhtasar Fazliddin qizi, Abdurakhmanova (International Journal of Business, Law, and Education, 2020)
Stability of the socio-economic conditions in the country, the rule of law, the size of the domestic market, rich natural resources, high intellectual potential, stability of the banking and financial system, development of infrastructure and logistics, flexibility of tax policy, participation of foreign investors in the privatization process, foreign capital privileges and preferences, such as the provision of additional facilities to the enterprises with the participation of foreign investors it serves as an important decision in favor of Development and strengthening of the banking system has always been in the focus of our attention, and this is giving its positive results. The country's banking system demonstrates stability and stability. This is explained by the high level of reliability of banks and the lack of reliance on foreign sources of financing, and the negative impact of external shocks. Investment activity of commercial banks is increasing. More than 75% of commercial banks' investments are long-term investment loans for over three years. In general, it should be noted that over the past ten years, lending by the banks to the real sector of the economy has increased 7 times. The unconventional approach to transfer the economically insolvent enterprises to the balance sheets of the banks has justified and proved effective. At present, out of 164 bankrupt enterprises transferred to the banks, 156 have fully restored their production activity, 110 have been sold to new investors. Commercial banks invested 275 billion soums in the technical re-equipment and modernization of such enterprises, resulting in over 22,000 jobs. The role of banks is particularly important in their investment policies for modernization, technical and technological re-equipment of leading sectors of the economy, housing construction, transport and infrastructure communications development. In this regard, commercial banks of the country have problems with the mechanism of lending, monitoring and repayment of loans and the need to develop scientific proposals and practical recommendations aimed at solving these problems.